A Series of Ternary Metal Chloride Superionic Conductors for High‐Performance All‐Solid‐State Lithium Batteries (Adv. Energy Mater. 21/2022). Issue 21 (2nd June 2022) - Liang, Jianwen; van der Maas, Eveline; Luo, Jing; Li, Xiaona; Chen, Ning; Adair, Keegan R.; Li, Weihan; Li, Junjie; Hu, Yongfeng; Liu, Jue; Zhang, Li; Zhao, Shangqian; et al.
Abstract : Solid State Li Batteries In article number 2103921, Marnix Wagemaker, Xueliang Sun and co‐workers report a favorable orthorhombic phase in various Li‐M‐Cl (M = Dy, Ho, Y, Er, Tm) systems which triggers a significant increase in Li + diffusivity and reduces the activation energy barrier for diffusion. The findings are expected to aid discoveries around the fundamental chemical theories of the rare earth metal halides and aid exploration of new materials with high Li + conductivity.